(untitled) (Cambridge, 1998)
The volume includes original papers dealing with different aspects of the interface between SLA and LT research. Second language acquisition (SLA) and language testing (LT) research have largely been viewed as distinct areas of inquiry in applied linguistics. In recent years, however, there has been greater overlap, or interface, between these two areas, and an increasing commonality of interests, both in terms of the research questions addressed and the empirical approaches taken in dealing with these questions. This paperback edition provides a fresh look at areas of common interest to both SLA and LT research, and ways in which research in these two areas of applied linguistics can be fruitfully integrated. The volume includes original papers dealing with different aspects of the interface between SLA and LT research. This collection thus constitutes a starting point for a continuing and expanding dialogue between SLA and LT researchers.
Keywords: Second language acquisition,Language; Research,Research,Ability testing